2020
DOI: 10.3390/v12060592
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus DNA is a Substrate for the cGAS/STING Pathway but is not Sensed in Infected Hepatocytes

Abstract: Hepatitis B virus (HBV) chronic infection is a critical risk factor for hepatocellular carcinoma. The innate immune response to HBV infection is a matter of debate. In particular, viral escape mechanisms are poorly understood. Our study reveals that HBV RNAs are not immunostimulatory in immunocompetent myeloid cells. In contrast, HBV DNA from viral particles and DNA replication intermediates are immunostimulatory and sensed by cyclic GMP-AMP Synthase (cGAS) and Stimulator of Interferon Genes (STING). We show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 65 publications
6
43
0
Order By: Relevance
“…In contrast to HDV, HBV replication does not activate significant innate immune responses [ 132 , 169 , 170 , 171 , 172 , 173 , 174 ]. Although some publications described HBV-induced IFN or pro-inflammatory responses [ 175 , 176 , 177 , 178 , 179 ], these responses are usually low and temporary compared to those activated by HDV.…”
Section: Crosstalk Between Hdv-induced Ifn Response and Hbvmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to HDV, HBV replication does not activate significant innate immune responses [ 132 , 169 , 170 , 171 , 172 , 173 , 174 ]. Although some publications described HBV-induced IFN or pro-inflammatory responses [ 175 , 176 , 177 , 178 , 179 ], these responses are usually low and temporary compared to those activated by HDV.…”
Section: Crosstalk Between Hdv-induced Ifn Response and Hbvmentioning
confidence: 99%
“…Although some publications described HBV-induced IFN or pro-inflammatory responses [ 175 , 176 , 177 , 178 , 179 ], these responses are usually low and temporary compared to those activated by HDV. Other studies showed that HBV pgRNA and DNA could be substrates of cellular PRRs [ 174 , 175 , 178 , 179 ]. However, such RNA/DNA is likely not reachable by PRRs in the cytoplasm due to shielding by the HBV capsid ( Figure 2 ).…”
Section: Crosstalk Between Hdv-induced Ifn Response and Hbvmentioning
confidence: 99%
“…These recent data have important conceptual implications in the interaction between cGAS, cellular components, and viral DNA in the nucleus, even though no direct interaction has been observed apart for HIV capsid so far. In this context, several lines of evidence suggest that the DNA genome of hepatitis B virus (HBV) stimulates cGAS activity and triggers the activation of the cGAS-STING pathway when transfected into hepatocyte-derived cells ( 33 , 86 ). However, no induction of innate immune pathways is detected upon viral infection ( 33 , 86 ).…”
Section: Cgas: a Main Actor Of Cellular Response To Dna And Rna Virusmentioning
confidence: 99%
“…In this context, several lines of evidence suggest that the DNA genome of hepatitis B virus (HBV) stimulates cGAS activity and triggers the activation of the cGAS-STING pathway when transfected into hepatocyte-derived cells ( 33 , 86 ). However, no induction of innate immune pathways is detected upon viral infection ( 33 , 86 ). The “stealth” pattern of this peculiar virus was initially attributed, in addition to the absence HBV RNAs sensing, to the protection of the genome within the capsid during its transport to the nucleus ( 87 ).…”
Section: Cgas: a Main Actor Of Cellular Response To Dna And Rna Virusmentioning
confidence: 99%
See 1 more Smart Citation